2006
DOI: 10.1016/j.jfe.2005.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Scale of harvesting by non-industrial private forest landowners

Abstract: We examine the intensity of harvesting decision by non-industrial landowners at the lowest price offer they deem acceptable, using a multiple bounded discrete choice stated preference approach that draws upon and connects two subfields of forestry, one identifying characteristics of landowners important to past harvesting or reforestation decisions, and another proposing how landowners evaluate price offers for forest harvesting decisions. Variables important to harvest intensity choices when the landowners fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…The literature review focussed on understanding the harvesting behaviour of forest owners (Beach et al, 2005;Bolkesjo et al, 2007;Butler, 2006;Favada et al, 2009;Stordal et al, 2008;Vokoun et al, 2006;Adams et al, 1991;Araño and Munn, 2006), as well as on wood supply in more general terms (Sterba et al, 2000;Verkerk et al, 2011). Based on our review and data availability for the entire study área, 16 potential location factors influencing the likelihood of harvest were identified, as well as a priori assumptions with regards to the direction of influence of each location factor on harvesting likelihood (Table 1).…”
Section: Location Factorsmentioning
confidence: 99%
“…The literature review focussed on understanding the harvesting behaviour of forest owners (Beach et al, 2005;Bolkesjo et al, 2007;Butler, 2006;Favada et al, 2009;Stordal et al, 2008;Vokoun et al, 2006;Adams et al, 1991;Araño and Munn, 2006), as well as on wood supply in more general terms (Sterba et al, 2000;Verkerk et al, 2011). Based on our review and data availability for the entire study área, 16 potential location factors influencing the likelihood of harvest were identified, as well as a priori assumptions with regards to the direction of influence of each location factor on harvesting likelihood (Table 1).…”
Section: Location Factorsmentioning
confidence: 99%
“…Most forest owners in the United States hold \4 ha of forest land, and their average tenure is 26 years (Butler 2008). We can also posit that absentee owners may have less diverse and/or smaller networks than resident owners, since property residence has been connected to decreased likelihood for management activities (Vokoun et al 2006;Joshi and Arano 2009). Finally, local institutions and county rules, such as logging permits, taxes, and zoning regulations, may create structural constraints or opportunities on social behavior because individual networks exist in multilevel environments that have their own network-like structures (Pescosolido 2006).…”
Section: Variations In the Network Of Forest Ownersmentioning
confidence: 99%
“…How American forest management on small forest holdings compared to that in European countries, especially Sweden, also became a research topic [174][175][176][177][178][179][180][181][182]. Some studies considered economic aspects of small forests [183][184][185][186][187][188][189][190][191][192][193][194], suggesting education and demonstration programs [195][196][197][198][199][200] or technical assistance [201][202][203][204][205][206][207][208] as means to encourage forest management. Even factors like ownership change impacted potential timber supply on NIPF forests [209][210][211][212][213][214][215][216][217][218].…”
Section: General Problems Of Promoting Management On Nipf Holdingsmentioning
confidence: 99%